Segnali di resilienza rispetto al Covid. I casi di Ostana e di Gandino - Sergio De La Pierre (Scienze del Territorio, 2020)
How did two municipalities in mountain areas, different from each other but similar for having since several years many civic associations, react to Covid? We ask this to many privileged witnesses. Ostana is a small virtuous municipality in Piedmont Alps, famous for its successful re-population projects, which experienced directly no Covid case so far, but has been able to take advantage from pandemic designing a new local development scenario. It has namely set up a community cooperative with projects aimed at sociality, tourism, place promotion, culture, neo-agriculture. Gandino, a municipality located in the Bergamasco area most severely hit by Covid, has counted hundreds of dead. Here resistance and solidarity by most people has been extraordinary, bringing many population components to imagine a different future for the after crisis. Resilience signals that in both situations meet the criterion of multisectoral local development, which is a fundamental key to community resilience.